Ethical Perspectives on the Reformulation of Labour Law Policy Governing Compensation Payments for Fixed-Term Contract Employees: Teori Etika Terhadap Reformulasi Kebijakan Hukum Ketenagakerjaan Pada Pembayaran Uang Kompensasi Pekerja PKWT - Asrofi, Muchtar Hasan (Universitas Islam Indonesia, 2025)
Government Regulation No. 35 of 2021 on Fixed-Term Employment Contracts, Outsourcing, Working Hours, and Rest Periods (PP No. 35/2021) has not yet established a mechanism for the payment of compensation to workers under fixed-term employment contracts (PKWT): whether it should be paid in a lump sum or in installments, and what the legal consequences are if paid in installments. In practice, there are employers who pay compensation in installments after the PKWT period ends (if not extended) or in installments/in full after the extension of the PKWT (if extended). The issue examined in this paper is: what is the perspective of ethical theory on the reformulation of labor law policy regarding compensation for PKWT workers? This study is a doctrinal/normative study using a conceptual approach. The data sources for this study are secondary data. The purpose of this paper is to analyze the role of ethical theory in the reformulation of labor law policies regarding compensation for PKWT workers. The findings of this study indicate that, first, according to rights theory (one of the ethical/moral theories), the provision of compensation in installments, to be paid in full after the extension of the PKWT, is ethically sound because it is oriented toward the fulfillment of rights, regardless of the outcome of the action. The rights theory bridges the differing perspectives of Article 15 (1) PP No. 35/2021, which views the installment payment of PKWT compensation favorably, with the perspective of Article 15 (4) of PP No. 35/2021, which views it unfavorably. Second, the author proposes amendments PP No. 35/2021 to clarify the mechanism for paying PKWT compensation, whether it must be paid in cash or may be paid in installments, including the consequences of such installment payments.